Effects of Stocking Density on Growth and Survival of Pearl Oyster Spat (Pinctada maxima) in Laboratory Rearing - Istiqomah, Santun Nur; Mukhlis, Alis; Mulyani, Laily Fitriani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Pearl oysters, Pinctada maxima, are one of the aquaculture commodities with high economic value and Indonesia has great potential in developing pearl oysters cultivation. However, the continuity of pearl production in Indonesia is highly dependent on the success of rearing spat (pearl oyster seedlings) in the initial growth phase in the laboratory. This study aims to evaluate the impact of stocking density on the growth and survival of pearl oyster spat during rearing in the laboratory. The research was conducted using an experimental method at the Pearl Oyster Breeding Laboratory of PT. Mutiara Surya Indonesia, West Nusa Tenggara Province. Various densities of pearl oyster spat (3, 6, 9, and 12 spat/L) were tested in 3 (three) replications using a Completely Randomized Design (CRD). The results showed that the treatment had a significant effect on the growth of the dorso-ventral shell length of pearl oysters spat (p<0.05). The highest growth after 21 days of maintenance was achieved in the treatment with a stocking density of 3 spat/l with absolute growth of 6.44 mm, relative growth of 304.09%, and daily specific growth rate of 6.88%/day. The highest survival rate was obtained at a stocking density of 3 spat/l, namely 94.4%. The results indicate that lower stocking densities tend to result in best growth and good survival rates for pearl oyster spat. It is advisable to experiment with higher densities of live feed to increase the efficiency and productivity of pearl oyster cultivation containers in the future. This study contributes significantly to understanding the factors influencing the growth and survival of pearl oyster spat in the context of aquaculture.